A política pública de formação de professores na modalidade a distância e o habitus do egresso do Curso de Licenciatura em Pedagogia da UEPG - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
At this moment, in which the economy globalization, the insertion of digital technologies and the expansion of neoliberalism, has become a reality, school education has become strategically questioned about its functions and contributions to this society, which is constantly on transformation. In Brazil, from the 1990s, there was an expansion of educational reforms, attributing education as the driving force for economic development and redirecting teacher training program. In this way, an expansionist process of Higher Education took place in the country, supported by the perspective of democratization, diversification and internalization of educational opportunities. The Education Law nº 9.394/1996 legalized these reforms through the recognition of distance Educational modality and the need for higher education for teachers to work in Basic Education. Thus, Public Higher Education, Teacher Training and Distance Education, markedly from 2005, with the creation of the Open University System of Brazil - UAB, reach the population, whose haven`t the right to guaranteed access yet. Therefore, this research aimed to study the public policy of teacher education in distance education through the Open University System of Brazil (UAB). In this sense, the general objective of the work was to analyze the changes by the policy of teacher training in the EAD mode provoked in the habitus of egress from the Pedagogy EAD Course of UEPG (2009-2012). The specific objectives were: a) to discuss the State as a metacamp of power and its conduct of educational public policies; b) to reflect on the relationship between the policy of expansion of Higher Education and the training of teachers in the distance education modality; c) to explain the Open University of Brazil and it’s UEPG implantation of the Pedagogy course; and d) to analyze in the trajectories of the egresses from the Course of Pedagogy EaD the changes occurred in its habitus in function of their teacher education in the EAD modality through the UAB System. The research was configured as a case study, therefore it adopted a qualitative approach. The theoretical foundation of the thesis was developed from the theory of Pierre Bourdieu (1989; 1998; 2001; 2003; 2008; 2012; 2014; 2015) on the conception of the state, the notion of the agent's field, habitus, capital and trajectory. In the field of teacher training, Gatti (2009; 2010) Gatti and Barreto (2009) Barreto (2015), Rabelo and Martins (2006) and Saviani (2009). In the field of Higher Education, De Paula (2016), Ferreira and Oliveira (2011), Mancebo (2004; 2017) and Sguissardi (2015; 2018) and in the field of Distance Education, Belloni (2003), Keegan (1996), Alonso (2010), Levine (2005), Mill et al. (2008) and Tarouco et al.(2011). The research was based on a documentary basis, such as: Laws, Decrees, Resolutions, Curricula of the Pedagogy Course, records on the history of UAB implementation and an empirical basis, involving the collection of data through questionnaires and interviews with the graduates of the Pedagogy course UAB/UEPG. Subjects was 81 (eighty-one) graduates of the Pedagogy Course of the UAB/UEPG who answered the questionnaire and 8 (eight) were interviewed. For the analysis of the data, four categories were established, which were expressed by the trajectories of the graduates, that is: a) family trajectory; b) school trajectory; c) professional trajectory; and d) possible trajectories. The results of this research indicated that the graduates broke with the causality of the probable and that when entering the Higher Education they expanded their cultural, social and economic capital, generating improvements in their performance and professional ascension, social recognition and incentive to the permanent and continuous education, as well as positively positioned themselves in relation to the beneficial ones of the public policy of teacher training offered through the UAB System. Based on these results, we confirm the hypothesis that the relationships established, the disputes experienced in the training field, the expansion of the different capitals that constituted the formative trajectories of the graduates, and the UAB's offer of the Pedagogy course at distance caused changes in its habitus, in order to lead to the improvement of the position of the agent in the field to which it is inserted and thus it is defended the thesis that the public policy of teacher training in the distance modality offered through the UAB System caused changes in the habitus of the graduates of the UEPG EaD Pedagogy Course (2009-2012).
The public policy of training teachers in the distance modality and the habitus of the graduate degree course in Pedagogy of UEPG
Keywords: Política Pública Educacional; Educação a Distância; Universidade Aberta do Brasil; Habitus; Egresso; Licenciatura em Pedagogia; Educational Public Policy; Open University of Brazil; Egress; Habitus; Degree in Pedagogy; CNPQ::CIENCIAS HUMANAS::EDUCACAO